Discordance between Clinical and Ultrasound Examinations in Juvenile Idiopathic Arthritis: An Experimental Approach - Francesco Licciardi; Marco Petraz; Carlotta Covizzi; Francesca Santarelli; Carlotta Cirone; Roberta Mulatero; Francesca Robasto; Marta Dellepiane; Silvana Martino; Davide Montin; Viviana Ravagnani (MDPI AG, 2022)
Clinical examination (CE) and musculoskeletal ultrasound (MSUS) of ten joints (knee, ankle, wrist, elbow, II-MCP) and their extra-articular (EA) compartments (tendons and bursae) were performed on 35 consecutive patients with active juvenile idiopathic arthritis (JIA) (active group) to test how the extension of MSUS examinations to EA changes the concordance between MSUS and CE. The overall concordance between CE and MSUS, measured with Cohen's Kappa (k), was moderate (k = 0.43); the addition of EA MSUS increased the concordance in all joints, with the exclusion of II-MCP (k = 0.49). In the ankle and wrist, the k increase was relevant (k from 0.13 to 0.27 and 0.11 to 0.41). In the active group patients, we observed 44 subclinical synovitis; the number of subclinical synovitis per patient was correlated with JADAS-27 (p = 0.03) and was higher in a control group composed of 15 patients with persistent disease remission (1.3 vs. 0.4 p = 0.03). Our results show that EA compartments should always be evaluated during MSUS. Furthermore, we demonstrate a moderate concordance between CE and MSUS in JIA; the finding of subclinical synovitis is common in patients with active diseases and is related to disease activity.